2018
DOI: 10.1101/422261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rare genetic variation and balanced polymorphisms are important for survival in global change conditions

Abstract: 17Standing genetic variation is important for population persistence in extreme 18 environmental conditions. While some species may have the capacity to adapt to predicted 19 average future global change conditions, the ability to survive extreme events is largely 20 unknown. We used single generation selection experiments on hundreds of thousands of 21Strongylocentrotus purpuratus sea urchin larvae generated from wild-caught adults to identify 22 adaptive genetic variation responsive to moderate (pH 8.0) and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 73 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The experimental acidification in the studies above utilized a low pH treatment within the bounds of what is frequently experienced by purple sea urchins in nature, pH 7.8 (900 ppm pCO 2 ; Hofmann et al, 2011;Evans et al, 2013Evans et al, , 2015. Rearing larvae in moderate (pH 8.0) and extreme (pH 7.5) low pH conditions, Brennan et al (2019) found purple urchin larvae to have adaptive standing genetic variation for survival in extreme low pH conditions that show correlated responses to moderate low pH conditions (Figure 4; Brennan et al, 2019). Interestingly, two classes of genetic variation emerge as useful for survival in low pH conditions: (1) variants that respond to both pH conditions and are maintained at high frequency in natural populations, and (2) relatively rare genetic variants that respond to either pH condition (Brennan et al, 2019).…”
Section: Testing the Genetic "Lottery" Hypothesis For Larval Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental acidification in the studies above utilized a low pH treatment within the bounds of what is frequently experienced by purple sea urchins in nature, pH 7.8 (900 ppm pCO 2 ; Hofmann et al, 2011;Evans et al, 2013Evans et al, , 2015. Rearing larvae in moderate (pH 8.0) and extreme (pH 7.5) low pH conditions, Brennan et al (2019) found purple urchin larvae to have adaptive standing genetic variation for survival in extreme low pH conditions that show correlated responses to moderate low pH conditions (Figure 4; Brennan et al, 2019). Interestingly, two classes of genetic variation emerge as useful for survival in low pH conditions: (1) variants that respond to both pH conditions and are maintained at high frequency in natural populations, and (2) relatively rare genetic variants that respond to either pH condition (Brennan et al, 2019).…”
Section: Testing the Genetic "Lottery" Hypothesis For Larval Selectionmentioning
confidence: 99%
“…Rearing larvae in moderate (pH 8.0) and extreme (pH 7.5) low pH conditions, Brennan et al (2019) found purple urchin larvae to have adaptive standing genetic variation for survival in extreme low pH conditions that show correlated responses to moderate low pH conditions (Figure 4; Brennan et al, 2019). Interestingly, two classes of genetic variation emerge as useful for survival in low pH conditions: (1) variants that respond to both pH conditions and are maintained at high frequency in natural populations, and (2) relatively rare genetic variants that respond to either pH condition (Brennan et al, 2019). These results emphasize (1) the importance of environmental variation that potentially leads to balancing selection in the maintenance of common adaptive variants (Levene, 1953), and (2) the importance of large population sizes for the maintenance of rare genetic variation that is adaptive in global change conditions.…”
Section: Testing the Genetic "Lottery" Hypothesis For Larval Selectionmentioning
confidence: 99%
See 1 more Smart Citation